2007
DOI: 10.1097/01.aog.0000251499.18394.9f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Educational Workshop on Performance of Fourth-Degree Perineal Laceration Repair

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 15 publications
2
32
0
2
Order By: Relevance
“…Previous studies 19,20 have shown that obstetrics-gynecology residents cannot identify OASIS properly, and therefore underreporting of these events may influence the recorded laceration patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 19,20 have shown that obstetrics-gynecology residents cannot identify OASIS properly, and therefore underreporting of these events may influence the recorded laceration patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Rating Scale (GRS) assesses seven aspects of surgical skill: respect for tissue, time, and motion, instrument handling, knowledge of instruments, flow of operation, use of assistants, and knowledge of the specific procedure, and includes an overall pass/fail assessment score (9). As in previous studies of this nature, the pretesting, teaching, and posttesting all occurred in the same half day session (14). Two senior gynecologic attending physician raters were used for assessing the resident's performance.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has demonstrated that the combination of the Objective Structured Assessment of Technical Skills (OSATS) and a written examination before and after an educational workshop is a valid and reliable way of assessing residents' improvement in surgical skills and knowledge in the repair of fourth-degree lacerations. 4,5 We sought to expand this work by including a 6-month follow-up OSATS and written examination to evaluate the retention of information learned during the workshop. We hypothesized that residents' technical skills and knowledge to repair fourth-degree perineal lacerations will reflect…”
Section: Introductionmentioning
confidence: 99%